2015
DOI: 10.4172/2157-7439.1000311
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Characterization of Traditional Homeopathically-Manufactured Silver (Argentum Metallicum) Medicines and Placebo Controls

Abstract: This exploratory study characterized nanoparticles (NPs) in homeopathically-prepared silver medicine (Argentum Metallicum), succussed and unsuccussed control solutions. Methods included nanoparticle tracking analysis (NTA), zeta potentials, inductively-coupled plasma mass spectroscopy (ICP-MS) for silver, and ultraviolet visible spectroscopy (UV-vis). Homeopathy is a 200 year-old traditional medical system using mineral, plant, and animal sources to treat patients. Debate over the efficacy of homeopathic medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 183 publications
(300 reference statements)
1
13
0
Order By: Relevance
“…The physicochemical properties of homeopathic remedies show that they contain low, but measurable, amounts of NPs [5, 6, 20, 24]. Advancements in the fields of nanoscience and nanotechnology have resulted in countless possibilities for consumer product applications, many of which have already migrated from laboratory benches onto store shelves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physicochemical properties of homeopathic remedies show that they contain low, but measurable, amounts of NPs [5, 6, 20, 24]. Advancements in the fields of nanoscience and nanotechnology have resulted in countless possibilities for consumer product applications, many of which have already migrated from laboratory benches onto store shelves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the wide differences regarding the amounts of dilution- from 30CH to 200CH, no significant differences in the shapes and the sizes of the particles from those in the original material were observed. In addition, recent studies indicated that homeopathically-prepared medicines (HMs) contain source NPs, silicates [5, 6, 11, 20, 24, 25, 26, 27, 28], and other less well-characterized nanostructures. However, the TEM images in this study did not confirm that these NPs were NPs of the starting material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotechnology researchers have begun to recognize similarities between the traditional, crude, mechanical attrition manufacturing techniques of homeopathy and the top-down approaches for making nanostructures from insoluble source materials used in modern nanotechnology. 1,2,4 Previous publications by Demangeat 7,13 using NMR relaxation have revealed the involvement of nanobubbles in nanometric superstructures in high potentizations.…”
Section: Introductionmentioning
confidence: 99%
“…Homeopathic ultra-high dilutions are used universally in the treatment of human, animal and plant diseases. Recent research publications of the author and many others demonstrated the presence of nanoparticles (NPs) in homeopathic ultra-high dilutions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. As ultra-high dilutions (UHDs) demonstrated the potential in regulating the growth [16][17][18][19][20][21][22][23][24][25][26] and effectiveness in treating a variety of plant diseases [27][28][29][30][31][32], it is decided to characterize one of the commonly used homeopathic plant remedies in India particularly in the state of Kerala.…”
Section: Introductionmentioning
confidence: 99%